2017
DOI: 10.1016/j.freeradbiomed.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal-induced AMPK activation leads to autophagic degradation of thioredoxin 1 and glyoxalase 2 in HT22 nerve cells

Abstract: Methylglyoxal (MGO) is a major glycating agent that reacts with basic residues of proteins and promotes the formation of advanced glycation end products which are believed to play key roles in a number of pathologies, such as diabetes, Alzheimer’s disease, and inflammation. We previously showed that MGO treatment targets the thioredoxin and the glyoxalase systems, leading to a decrease in Trx1 and Glo2 proteins in immortalized mouse hippocampal HT22 nerve cells. Here, we propose that autophagy is the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
2
24
2
Order By: Relevance
“…Accumulating evidence indicates that mitophagy is activated as an adaptive response to oxidative stress and mitochondria damage [ 33 , 34 , 35 ], and we investigated the activation of mitophagy in MG-exposed brain ECs. The formation of autophagosomes was increased following MG treatment, as measured by immunostaining of microtubule-associated proteins 1B light chain 3B (LC3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that mitophagy is activated as an adaptive response to oxidative stress and mitochondria damage [ 33 , 34 , 35 ], and we investigated the activation of mitophagy in MG-exposed brain ECs. The formation of autophagosomes was increased following MG treatment, as measured by immunostaining of microtubule-associated proteins 1B light chain 3B (LC3B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Zhang et al [35] demonstrated that HIF-1 negatively regulated the gene expression of Glo-1 in leukemia stem cells. Dafre et al [33] demonstrated that autophagy inhibitors (bafilomycin A and chloroquine) reversed Glo-2 degradation induced by MG. Since we have shown that MG treatment induces HIF-1 degradation and autophagy activation, these mechanisms might affect the expression levels of Glo-1 and Glo-2 in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Compatible with this suggestion is the finding that knockdown of glyoxalase-1 in non-diabetic mice results in renal lesions indistinguishable from those of diabetic mice, while overexpression of glyoxalase-1 in diabetic mice prevents the development of nephropathy 18 . Other studies have shown that MGO impairs HIF-1α degradation and signaling 19,20 and activates AMPK mediated autophagic degradation of thioredoxin 1 21 , thus emphasizing its influence on redox homeostasis 22 . Despite the clear association between reactive carbonyl species and diabetic complications, their mode of action on endothelial cells is discussed ambiguously 2327 .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, we have noticed that the functional abundance of Thioredoxin (Trx) is not elevated (supplementary material, Table S2), which may be that aldehydes restrict the activity of Thioredoxin (Trx). Indeed (Dafre et al 2017), some aldehyde molecules including malondialdehyde (MDA), trans-2-hexenal and 4-hydroxynonenal were proved to function as powerful gene activators despite their potential toxicity. Our research shows that changes in salinity on the structure of bacterial communities are obvious, but the impact on bacterial function is limited.…”
Section: Discussionmentioning
confidence: 99%